(untitled) (Journal of Finance, Business and Management Studies, 2024)
The pervasive use of social media platforms has become integral to daily life, offering unique opportunities for communication, information sharing, and social connection. However, concerns about the potential drawbacks and risks, particularly mental well-being, have prompted extensive research. This article presents a scoping bibliometric review of the literature on the association between social media and mental health. The study conducts a thorough examination using the Dimensions database, related to "Mental Health" and "Social Media" keywords. A total of 500 highly significant ones were selected based on citations. Utilizing VOS Viewer and Biblioshiny, the analysis maps the current landscape, revealing trends, influential countries, publications, and author interconnections. The findings highlight the global impact of research efforts, emphasizing collaborative and impactful contributions from various nations. The absence of international collaboration among authors presents a promising avenue for future exploration. This comprehensive analysis is a valuable resource, guiding researchers, policymakers, and practitioners in navigating the digital age’s intricate relationship between mental well-being and social media.